Feasibility and Safety of Laparoscopic Hydatid Surgery: A Systematic Review - Citgez, Bulent; Battal, Muharrem; Cipe, Gothan; Karatepe, Oguzhan; Muslumanoglu, Mahmut (My University, 2013)
Background/Aims: Eccinococal disease is an important problem in regions such as Turkey, where tapeworms are endemic. Surgery is the main key to successful treatment. Among the various techniques, laparoscopy has recently come to be preferred over the commonly used open technique. The aim of this review was to evaluate the feasibility safety and potential benefits of laparoscopic hydatid surgery. Methodology: Three independent investigators conducted comprehensive research using PubMed, MEDLINE, Embase and the Cochrane library Language was restricted to English; reference lists were searched manually. Results: Tweny-two retrospective studies were selected for review, none of which were randomized controlled trials. It was found that the laparocopic approach was attempted in 666 patients. The overall conversion rate to laparotomy was 4% (27/666) with a recurrence rate of hydatid disease of 1.6% (11/666). Average length of hospital stay was 4.7 (1-30) days. Conclusions: Based on this meta-analsysis, evidence confirms that the laparoscopic surgical technique is feasable and safe. Good randomized controlled trials are lacking.